Calculation Model and Method of Gain-Loss Game Distribution Mechanism on Projectile and Target Intersection Confront - Yun Hao; Hanshan Li (IEEE Access, 2023)
Aiming at the problem of damage calculation under the confront game mechanism formed by the projectile and target intersection in the weapon range damage test, this paper proposes a target damage calculation model and method of gain-loss game distribution mechanism on projectile and target intersection confront based on the characteristics of the projectile and target intersection confront game. In this method, the damage of the confront game between the projectile and the target is regarded as the participants of the two-person zero-sum non-cooperative game. According to the gain-loss relationship between the participants of the projectile and the target, we establish a damage assessment calculation model with the confront game between the projectile and the target, and derive the payoff function of the attack-defense game between the projectile and the target. We also establish a target damage calculation model with value / cost index function, determine the value / cost index function of projectile attack target, and give the calculation algorithm of projectile attack target damage based on game theory, and also research the allocation method of projectile attack target based on value / cost index function, at last, give the optimized target damage evaluation system. Through quantitative calculation and analysis, it is found that the effect of target damage is different under different conditions of game strategies, especially the value of value / cost index function is different. The obtained game damage probability presents a random number of Gaussian distribution. When the optimal distribution value is satisfied, the target damage effect is the best, which verifies the scientific type and rationality of the damage calculation model proposed in this paper.